Comparative study on tannin content of Bakauan (Rhizophora sp.), kamachili (Pitchecolobium dulce) and ipil-ipil (leucaena glauca). - Salcedo, Leonida E.
Tannin from the barks of bakauan (Rhizophora sp.), kamachili (Pithelcolobium dulce) and ipil-ipil (Leacaena glauca) were extracted with water and alcohol-ether mixture at 80 degrees centigrade with 1:8 bark to water ratio. Qualitative analysis and quantitative determination of tannin contents in the barks were also conducted for each species., Qualitative tests gave positive results for the presence of tannin in the three species. Tannin gave a white, yellow brown and greenish or bluish-black precipitates with gelatin acetic acid-lead acetate and ferric chloride tests respectively. Quantitatively, bakauan bark gave the highest percent tannin content of 19.91 followed by kamachili of 16.32 and ipil-ipil of 11.97. Tannin from kamachili and ipil-ipil was not found to be comparable to that of bakauan as a commercial source of tannin.